Democracy Assistance to Global South: A Case Study of Konrad-Adenauer Stiftung (KAS) Freedom Agenda in Indonesia - Tsabita Afifah Khoirunnisa; Yusli Effendi (Institute of International Studies, 2023)
This paper aims to investigate and analyze the democracy promotion carried out by Konrad-Adanauer Stiftung (KAS) in Indonesia. Our provisional findings on the case show that the hegemony of the North over the South is also perpetuated through political and economic assistance. Through the German political foundation of KAS, Germany seeks to foster a Western